Three-dimensional Evaluation of Maxillary Sinus Volume in Different Sex Groups Using Cone-beam Computed Tomography (Medico Legal Update, 2020)
Background/Objectives: Determining the sex of corpses is the first step of identification in a forensic analysis. Accurate anatomical knowledge for the maxillary-sinus serves as an important mediator of forensic sex determination.Method/Statistical Analysis: This study included 57 patients (27 males and 30 females) of Dan-kook university dental hospital. Cone-beam computed tomography data images were imported and reconstructed into Three-dimensional models by an interactive medical image control system, Mimics 17.0 software. This study was analyze at 95% significance level using SPSS Version 20.0. The independent t-test was performed to compare the measured values among the two experimental groups.Findings: The volume of the maxillary sinus measured with traditional radiography may differ from its actual size. The maxillary sinus can be more accurately measured using a 3D model restructured using the CBCT data as the 2D base compared to simple linear measurement in 2D model. In the present study, sex-specific volumes of the maxillary sinus were measured using a 3D model, and there were no significant differences in the volumes between the left and right for both men and women. However, between sexes, the mean left sinus volume was significantly greater among men (23.25) than women (17.59) (p